MENAKAR EKSISTENSI HOMESCHOOLING SEBAGAI MODEL PENDIDIKAN ALTERNATIF - Muhammad Asbar, Andi (Journal of Applied Transintegration Paradigm, 2022)
Abstract: Homeschooling is now present as an alternative education model for parents in directing their children to learn to develop their talents and interests without going through formal school. This study aims to reveal the reasons parents choose homeschooling and the attention of formal institutions such as schools. As well as, examine the existence of homeschooling in the perspective of psychology, sociology, and economics. This study uses a library research method or literature study, namely by conducting literature/reference studies, and journals that are relevant to the research. The results of this study reveal that first, parents choose homeschooling over school, due to dissatisfaction with school, students burdened with curriculum, bullying, brawls, and security reasons. In fact, many students experience sexual problems at school. Second, in the context of psychology. Homeschooling makes children not feel pressured in learning, but what parents are wary of is the child's psychological development. Third, from the sociological aspect, children who choose homeschooling will lose many things, especially aspects of communication with their peers, and live in learning groups that are only experienced by children at school. And fourth, from an economic point of view, of course, parents as users or customers of the homeschooling education model must pay relatively high costs. Only those from the upper middle class can achieve homeschooling. Keywords: Homeschooling, Alternative Education Model